2019
DOI: 10.3892/etm.2019.8229
|View full text |Cite
|
Sign up to set email alerts
|

Changes of complement and oxidative stress parameters in patients with acute cerebral infarction or cerebral hemorrhage and the clinical significance

Abstract: Changes of complement and oxidative stress parameters in patients with acute cerebral infarction (ACI) or cerebral hemorrhage (CH), and their clinical significance were explored. A total of 122 patients with ACI or CH admitted to the People's Hospital of Zhangqiu Area from August 2018 to September 2019 were collected. There were 59 ACI patients assigned into a cerebral infarction group (CIG) and further 63 CH patients in a cerebral hemorrhage group (CHG). Additionally, 53 healthy people in physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Studies have determined that the level of SOD in patients with cerebral hemorrhage (113.62 ± 9.14 U/mL) is significantly lower than healthy (161.20 ± 21.12 U/mL) [ 65 ]. It is a common indicator for evaluating oxidative stress in mouse models of ICH [ 2 , 6 , 56 , 58 , 66 , 67 ].…”
Section: Markers For Detecting Os After Ichmentioning
confidence: 99%
“…Studies have determined that the level of SOD in patients with cerebral hemorrhage (113.62 ± 9.14 U/mL) is significantly lower than healthy (161.20 ± 21.12 U/mL) [ 65 ]. It is a common indicator for evaluating oxidative stress in mouse models of ICH [ 2 , 6 , 56 , 58 , 66 , 67 ].…”
Section: Markers For Detecting Os After Ichmentioning
confidence: 99%
“…Current studies have revealed that there was a sixfold increase in C9 around the hematoma 24 h after ICH, and MAC and clusterin also increased in the perihematomal tissue 3 days after ICH ( 7 , 26 ).The anaphylatoxins C3a and C5a were upregulated after ICH: the level of C3a increased within 5 days after ICH, whereas the level of C5a peaked on day 3 and began to decrease ( 27 ). In a clinical study, patients with cerebral hemorrhage had higher C3 levels and lower C4 levels in serum than healthy people ( 28 ). Our study confirmed that the complement system and two complement pathways were upregulated after ICH at the transcriptive level in mouse brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that [16,17], oxidative stress runs through the whole pathogenesis of acute cerebral infarction. After brain injury and ischemia, a large number of free radicals are accumulated in cells.…”
Section: Discussionmentioning
confidence: 99%